Historical blocking: TZ 2020-10-27 to 2020-10-28 (Tanzania) - Voidly (2020)
CRITICAL severity censorship detected in Tanzania. Confidence: 89%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: TZ-2020-0005
Keywords: censorship; TZ; censorship; critical